Nye tiltag i grammatikundervisningen - Andersen, Vibeke (HERMES - Journal of Language and Communication in Business, 2002)
The author discusses the disadvantages of traditional grammar teaching from a didactic and learning perspective. Traditional grammar teaching is typically based on a theoretical introduction by means of system-orientated grammars, followed by product-orientated training. Due to the disadvantages of traditional grammar teaching, the author suggests replacing system-orientated grammars with holistic grammars and product-orientated training with comprehension-orientated training. A holistic grammar integrates systemic and pragmatic linguistic description with a view to making grammar relevant and interesting to the learner, while comprehension-oriented training moves focus away from production and on to comprehension for the purpose of promoting learning.